2011
DOI: 10.1155/2011/101848
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of MHC and Immunoglobulins A and E on Host Resistance to Gastrointestinal Nematodes in Sheep

Abstract: Gastrointestinal nematode parasites in farmed animals are of particular importance due to their effects on production. In Australia, it is estimated that the direct and indirect effects of parasite infestation cost the animal production industries hundreds of millions of dollars each year. The main factors considered by immunologists when studying gastrointestinal nematode infections are the effects the host's response has on the parasite, which immunological components are responsible for these effects, genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 115 publications
(138 reference statements)
1
20
0
Order By: Relevance
“…() and Lee et al . (), who reported that there is no single mechanism of nematode resistance in sheep. Lee et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Lee et al . (), who reported that there is no single mechanism of nematode resistance in sheep. Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al . (), however, also highlighted that the complex heterogeneity of results can be due to differences in environmental conditions, nutritional status of the animals, geographical locations and the large variety of gastrointestinal nematode parasites. However, this diversity is found in our combined dataset, and despite this diversity, significant regions were still found.…”
Section: Discussionmentioning
confidence: 99%
“…Of these the most practical and widely used indicator is FEC, which is moderately heritable and shows wide variability among individuals (Bishop and Morris, 2007;Safari et al, 2005). Resistance to GIN infection, as defined by a relatively low FEC, can manifest as a lower number of nematodes, reduced size of adult nematodes, reduced fecundity of females, increased proportion of inhibited larvae, or a combination of the foregoing elements (Balic et al, 2000;Lee et al, 2011). A reduction in either the number of fecund adult females or in female fecundity would have the beneficial effect of reducing worm contamination on pasture (Good et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism of breed resistance towards GI in general and H. contortus in specific is not due to single entity, as it is correlated with activation and production of high level of immunoglobulins (Michael et al, 2004;Lee et al, 2011), mast cells, eosinophils (Alba-Hurtado and Muñoz-guzmĂĄn, 2013), high amines level (Rothwell et al, 1971), interleukins (Corley and Jarmon, 2012a;, and influence of genetics of the breed. Resistant breeds show better expression of these substances than susceptible ones.…”
Section: Discussionmentioning
confidence: 99%